2022
DOI: 10.3390/s22082970
|View full text |Cite
|
Sign up to set email alerts
|

Two-Way Communication Digital Power Controllers for Wireless Retinal Prosthesis Systems

Abstract: Power-efficient digital controllers are proposed for wireless retinal prosthetic systems. Power management plays an important role in reducing the power consumption and avoiding malfunctions in implantable medical devices. In the case of implantable devices with only one-way communication, the received power level is uncertain because there is no feedback on the power status. Accordingly, system breakdown due to inefficient power management should be avoided to prevent harm to patients. In this study, digital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…As a result, the retina chip achieved a maximum stimulus period of 20 Hz, and a current deviation under 1.2 μA on the standard deviation of the overall stimulus current. For future work, the proposed high-density stimulation chip will be merged with a wireless power transmission system [ 20 ] and packaged for clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the retina chip achieved a maximum stimulus period of 20 Hz, and a current deviation under 1.2 μA on the standard deviation of the overall stimulus current. For future work, the proposed high-density stimulation chip will be merged with a wireless power transmission system [ 20 ] and packaged for clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, numerous studies have demonstrated the beneficial effects of administering appropriate electrical stimulation to humans, such as for treating diseases, reducing pain, and replacing the function of existing nerves [ 1 , 2 , 3 , 4 ]. To provide a glimpse into the ongoing research on electrical stimulation, we introduce several examples of spinal cord stimulation and retina prosthesis research.…”
mentioning
confidence: 99%
“…Zawawi R.B.A. et al proposed the addition of back telemetry to a retina prosthesis system which wirelessly transmits power, allowing the external transmitter to confirm whether the transmitted power is being received successfully by the system [ 2 ]. Moreover, in the event of abnormal reception, the receiver is designed to stop functioning until successful reception is achieved.…”
mentioning
confidence: 99%